On the Geographical Dispersion of Euro Currency Trading: An Analysis of the First 20 Years and a Comparison to the RMB - Frank Westermann (Comparative Economic Studies, 2022)
The Euro and the RMB are both relatively new currencies traded on the global foreign exchange market. While the Euro was introduced in 2001, China started cross-border settlement in RMB in 2009. We analyse the evolution of Euro trading based on data from the BIS triennial survey and compare the patterns to the experience of RMB internationalization. We find that—similar to the RMB—Euro trading displayed some convergence to the geographical pattern of all currencies in the first years of its existence. Thereafter, the convergence process appears to have come to halt. We document that the determinants of Euro trading include links to offshore trading centres, economic and institutional characteristics, but these turn out to be rather unstable over time. The RMB, in comparison, displays a clear convergence pattern and is more strongly influenced by policies and recent trade disputes. Furthermore, we compare the geographical dispersion of Euro trading to the previous D-Mark period and to other commonly used international currencies. These results help to interpret the evidence on initial convergence as a rebound effect from a decline in the international use of the D-Mark during the 1990s.
Keywords: C24; F31; F33; G15; G18; 330; FX Turnover; Geographical Trading Pattern; Euro and RMB Internationalization